Fumonisin occurrence in wheat and wheat by products - Cendoya, Eugenia (2021)
Wheat is the most important cereal consumed by the Argentine population. When Fusarium graminearum (main pathogen associated with FHB wheat disease in Argentina) was not the main Fusarium sp. species isolated from wheat, it was F. proliferatum, and fumonisins (FBs) were present in durum wheat grains. FBs contamination in common and durum wheat samples, and in wheat-based products (from supermarkets) in Argentina using HPLC-MS/MS was analyzed. Considering F. proliferatum as the responsible for FB presence in wheat, two ecophysiological surveys were made in a wheat based-medium and in irradiated wheat grains, and relative FUM8 and FUM19 genes expression was analyzed. As a result, 93% and 100% of wheat samples and wheat-based products, showed FBs contamination (0.15 - 1304.39 ng/g), (0.04 - 18.94 ng/g), respectively. Optimal aW levels for growth rate ranged from 0.995 to 0.96 at 25?30 °C. Maximum FBs amounts were obtained at higher aW at 25 or 15 °C. FB production profiles for each strain were related to temperatures. FUM genes expression at 25 °C correlated with FBs production, but not at 15 °C, where FBs production was lower and FUM genes were expressed as at 25 °C. This is the first report on FBs in common wheat and wheat-based products in Argentina